Hubungan Kebiasaan Konsumsi Kopi dan Kualitas Tidur dengan Status Gizi pada Remaja di Kelurahan Jagakarsa Jakarta Selatan - Tri Ardianti Khasanah; Fela Safilah (Universitas Negeri Medan, 2023)
The body has the hormones leptin and ghrelin that regulate appetite. An imbalance of these two hormones can result in changes in metabolism.. Currently, most adolescents consume excessive coffee which can cause metabolic disorders such as obesity. The purpose of this study was to analyze the relationship between coffee consumption and sleep quality with nutritional status in adolescents in Jagakarsa Village, South Jakarta. This research design uses cross sectional. Data collection using questionnaires by interviewed that have been tested for validity and anthropometric measurements of height and weight. The subjects in this study amounted to 95 people. Conducted in May - June 2022 Analysis of the relationship between coffee consumption variables and sleep quality with nutritional status using Chi-Square statistical test analysis. The results showed that most of the adolescents had normal nutritional status, namely 48 respondents. Coffee consumption habits based on frequency were mostly in the 1x / day category as many as 74 respondents, and based on quantity most were in the 1-2 cup / day category as many as 90 respondents. Sleep quality in the good category was 23 respondents and the bad category was 72 respondents. This study shows that there is no relationship between coffee consumption and nutritional status based on frequency (p=0.107), based on quantity of coffee consumption (p=0.090) and there is no relationship between sleep quality and nutritional status (p=0.116) in adolescents in Jagakarsa Village, South Jakarta. The conclusion of this study is that there is no significant relationship between coffee consumption variables and nutritional status. There is no significant relationship between sleep quality variables and nutritional status among adolescents in Jagakarsa Village, South Jakarta